CAN A CAPITAL OF EU REPRESENTED AS AN ARCHITECTURAL SPACE? SOFT CAPITAL VS. HARD CAPITAL? - Sagdic, Zafer; Erenoglu, Tulay (STEF92 TECHNOLOGY LTD, 2014)
In the 21st century EU is one of the super-power of the World while the definition of the union has been produced since the Middle Ages, more than this it is known that the definition of Europe has been produced since the Antique regarding to the economic, sociological, cultural and politic conditions. Although the idea of the united Europe had existed since the Middle Ages, till the 19th century, it is known that the idea could not turned into the reality. Unless after the 19th century and the early 20th century, the ideal construction of the united Europe had found a place in economic and sociological senses and in the build environment, as well. In the mid-20th century, after the two World wars, which affected Europe both physically and sociologically, the idea of Europe was finally institutionalized. The cities are the meeting points of policies and the citizens and the architecture is the tangible reflections of the ideologies and the organizations, due to these characteristics they become the biggest domain of the European Union. Architecture also has been used, as an important tool to achieve legitimacy and it is a proof of the existence of the governments during the pre-modern and modern eras. Chronologically, since 1980's it is known that under the effects of the new form of capitalism, parallel to the Keynesian theories and in 2010's under the effects of Crounch's non-death of capitalism as in the identity of neo-liberal economies, searching of the theme is born on the praxis of the architecture. Thus, the aim of the paper will be analyzing of the capitals of European Union in both the architectural and urban aspects, with respect to the problematic of representation and the concepts of Umberto Eco's Soft Capital vs. Rem Koolhaas's Hard Capital.
Keywords: European Union; capital cities; architecture; urban; Keynesian theories; Arts & Humanities - Other Topics